BASIC EDITION FOR NATURAL SCIENTISTS - Міщенко, Л. В. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
Review on a monograph G.I. Rudko, O.M. Adamenko “Groundlogy. Ecology-resource safety of Earth”. – C.: Academpress, 2009. – 512 p.